High temperature fatigue characteristics of P/M and hot-forgedW-Re and TZM for X-ray target of CT scanner - Harimon, Mohd Azhar; Miyashita, Yukio; Otsuka, Yuichi; Mutoh, Yoshiharu; Yamamoto, Shinichi (Elsevier, 2018)
The fatigue strengths at 1000 °C of layeredW-Re/TZM, bulkW-Re and bulk TZM for x-ray target materials were successfully evaluated under load-controlled four-point bending by introducing a fatigue failure criterion as twotimes increase of initial compliance. The obtained fatigue strengths at 1000 °C for layered W-Re/TZMand bulkWRe were similar and 280 MPa and 290 MPa at 106 cycles, respectively, while that of bulk TZM was 200 MPa. During fatigue loading at 1000 °C, dominant fatigue damage would be multiple intergranular crack nucleation and propagation,whichwould induce the increase of compliance. The reasonability of the fatigue failure criterion was confirmed by the fatigue process observations and the results of room temperature fatigue tests of the specimens tested at 1000 °C up to the cycles corresponding to the fatigue failure criterion.